2001
DOI: 10.4049/jimmunol.167.3.1803
|View full text |Cite
|
Sign up to set email alerts
|

AChlamydiapneumoniae-Specific Peptide Induces Experimental Autoimmune Encephalomyelitis in Rats

Abstract: It has been reported recently that the bacterial respiratory pathogen Chlamydia pneumoniae is present in the cerebrospinal fluid of a subset of multiple sclerosis (MS) patients. However, it is not known whether this organism is a causative agent of MS, or merely an opportunistic pathogen that takes advantage of a disease process initiated by some other means. We report identification of a 20-mer peptide from a protein specific to C. pneumoniae which shares a 7-aa motif with a critical epitope of myelin basic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 32 publications
0
44
0
2
Order By: Relevance
“…Third, the immune response can be focused on selected conserved epitopes, a key advantage for pathogens with high sequence variability but that may also prove valuable for Chlamydia given the reported intrastrain and interstrain variation in Cpn (42,43) and the evidence supporting selection of Ct escape mutants by anti-MOMP T cell responses (44). Fourth, potentially immunopathogenic epitopes can be excluded such as those in chlamydial Omp2 and in the Cpn0483 gene product, that respectively cause autoimmune myocarditis in mice and encephalomyelitis in rats (45,46). Finally, the use of epitopes can incorporate determinants from Ags that might be differentially expressed at specific stages of pathogen development or during persistence, a factor of crucial importance in the case of Chlamydia.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the immune response can be focused on selected conserved epitopes, a key advantage for pathogens with high sequence variability but that may also prove valuable for Chlamydia given the reported intrastrain and interstrain variation in Cpn (42,43) and the evidence supporting selection of Ct escape mutants by anti-MOMP T cell responses (44). Fourth, potentially immunopathogenic epitopes can be excluded such as those in chlamydial Omp2 and in the Cpn0483 gene product, that respectively cause autoimmune myocarditis in mice and encephalomyelitis in rats (45,46). Finally, the use of epitopes can incorporate determinants from Ags that might be differentially expressed at specific stages of pathogen development or during persistence, a factor of crucial importance in the case of Chlamydia.…”
Section: Discussionmentioning
confidence: 99%
“…This possible autoimmunity etiology in autism has been supported by detection of antibodies to nine different neuronspecific antigens and their cross-reactive peptides from miIk, C.pneumoniae and Streptococcus group A (I, 14,16). In this manuscript, we suggest a role for dietary proteins (milk and wheat), bacterial toxins (bacterial enterotoxins) and metals, such as mercury, in the pathogenesis of autistic behavior.…”
Section: Discussionmentioning
confidence: 92%
“…In fact, by reviewing the scientific literature, we found that over 60 different microbial peptides have been reported to cross-react with human brain tissue and MBP that induce T-cell responses but can also induce experimental autoimmune encephalomyelitis (14)(15)(16). Using the recent observation that maternal infection increases risk for schizophrenia and autism in offspring, respiratory infection of pregnant mice (both BALB/c and C57BLl6 strains) with the human influenza virus have resulted in offspring that displayed highly abnormal behavioral responses as adults.…”
mentioning
confidence: 99%
“…Current knowledge supports a multifactorial aetiology in which both genetic and environmental factors (including microbial agents) may concur. Interestingly, experimental autoimmune encephalomyelitis (EAE), the experimental animal model of multiple sclerosis, has been successfully induced using a C. pneumoniae peptide analogue of rat myelin basic protein [11]. Although multiple sclerosis and EAE are obviously two different entities, this study provides the first indication of a possible direct contribution of C. pneumoniae to the pathophysiology of (experimental) demyelination.…”
mentioning
confidence: 92%